ChemInform Abstract: Modified Julia Olefination on Sugar‐Derived Lactones: Synthesis of Difluoro‐exo‐Glycals. Issue 24 (June 2015) - Habib, Samuel; Gueyrard, David
Abstract: A Smiles rearrangement—elimination sequence is developed which allows the preparation of various title compounds without isolation of the intermediate hemiketal.